2023
DOI: 10.3389/fnbeh.2023.1175067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mindfulness and fatigue on emotional processing: an event-related potentials study

Abstract: Fatigue is a common experience in everyday life. People who experience fatigue will have more intense negative emotions, and at the same time, their positive emotions will decrease, impairing the individual’s emotional processing ability. In previous research, mindfulness meditation reduces the intensity of negative emotional stimuli. However, if individuals continue to be affected by negative emotions when they are fatigued, it is unclear whether mindfulness can buffer the negative association between fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 73 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Top-down regulation decreases emotional reactivity through engagement of prefrontal brain regions by means of active reinterpretation and reappraisal of the meaning of emotional stimuli. 24 It is understood that mindfulness may enact similar top-down and bottom-up regulatory processes for physical symptoms such as fatigue 25 and sleep. 26 For example, mindfulness might assist bottom-up activation by aiding in the reorientation of attentional processes to be open, curious, and accepting of present moment experiences of fatigue or sleep disturbance without judgement of embellishment.…”
Section: Introductionmentioning
confidence: 99%
“…Top-down regulation decreases emotional reactivity through engagement of prefrontal brain regions by means of active reinterpretation and reappraisal of the meaning of emotional stimuli. 24 It is understood that mindfulness may enact similar top-down and bottom-up regulatory processes for physical symptoms such as fatigue 25 and sleep. 26 For example, mindfulness might assist bottom-up activation by aiding in the reorientation of attentional processes to be open, curious, and accepting of present moment experiences of fatigue or sleep disturbance without judgement of embellishment.…”
Section: Introductionmentioning
confidence: 99%
“…Among Chinese university students, this can also be attributed to academic workload and employment concerns [31]. Fatigue and sleep issues are often interrelated and are associated with impairments in physical and mental health, cognition, emotions, and well-being [7,13,19,20]. Previous studies have shown that exercise interventions can be bene cial for fatigue and sleep issues [3,8,17].…”
Section: Introductionmentioning
confidence: 99%